Ideal Data to Determine Accurate Fajr Time - Adi Damanhuri; Akhmad Mukarram (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2022)
Early fajr time research was carried out by various parties with various techniques, one of which was using a sky quality meter (SQM) photometric tool. Observational data from various regions that have varying night levels result in a varying early fajr time as well. By paying attention to the effect of sky quality represented by the night level at the observation location, this research wants to answer whether the 20 mpsas night level limit is ideal data by looking at the correlation coefficient between night level and the turning point solution. From 1068 data with varying night levels, the correlation coefficient ( ) between the night level and the turning point solution is 0,42 which means there is an effect, while for data with a minimum night level of 20mpsas the correlation coefficient is 0,07 which means there is no influence. Based on the results of the analysis, the night level of 20mpsas can be the minimum limit for conducting an ideal early fajr time research. From 241 ideal observation data from 6 LAPAN observation stations, early fajr time presents when the Sun's elevation angle is -16,51°. Early fajr time is also the beginning of subuh prayer time, with its standard used in Indonesia, which is -20° or 3,49° different from the analysis results, if it is converted there is a difference of 13 minutes 57 seconds.